Campus action against sexual assault: needs, policies, procedures, and training programs - Paludi, Michele Antoinette (Women's psychology, 2016)
"Because women's work is never done and is underpaid or unpaid or boring or repetitious and we're the first to get fired and what we look like is more important than what we do and if we get raped it's our fault and if we get beaten we must have provoked it and if we raise our voices we're nagging bitches and if we enjoy sex we're nymphos and if we don't we're frigid and if we love women it's because we can't get a "real" man and if we ask our doctor too many questions we're neurotic and/or pushy and if we expect childcare we're selfish and if we stand up for our rights we're aggressive and "unfeminine" and if we don't we're typical weak females and if we want to get married we're out to trap a man and if we don't we're unnatural and because we still can't get an adequate safe traceptive but men can walk on the moon and if we can't cope or don't want a pregnancy we're made to feel guilty about abortion and for lots of other reasons we are part of the women's liberation movement"--